2021
DOI: 10.5713/ajas.20.0111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary selenium from selenium-enriched kale sprout, selenomethionine, and sodium selenite on performance and selenium concentrations in the tissues of growing quails

Abstract: Objective: This study aimed to determine the effect of dietary selenium (Se) from Se-enriched kale sprout (SeKS), selenomethionine (SeMet), and sodium selenite (SS) on performance, carcass characteristics and Se concentrations in the tissues, and to study the relationship between Se concentrations in muscle and feather in growing quails.Methods: The 320 quails (7 d of age) were divided into four treatments, according to a completely randomized design. The treatments were T1: control diet; T2, T3, and T4: contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Se concentration in basal diet has been highlighted. Previous studies in laying hens, broilers and quails also found that Se concentration in the basal diets met or slightly exceeded their respective requirements, ranging from 0.11 to 0.25 mg/kg [12,13,16,33], implying that conventional feed ingredients commonly used in poultry diets in Thailand and other countries in the region contain adequate Se for egg production. However, no data on total Se concentration and Se species in animal feedstuffs is available to confirm this speculation.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
“…Se concentration in basal diet has been highlighted. Previous studies in laying hens, broilers and quails also found that Se concentration in the basal diets met or slightly exceeded their respective requirements, ranging from 0.11 to 0.25 mg/kg [12,13,16,33], implying that conventional feed ingredients commonly used in poultry diets in Thailand and other countries in the region contain adequate Se for egg production. However, no data on total Se concentration and Se species in animal feedstuffs is available to confirm this speculation.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
“…SeY supplementation increased Se concentration in the meat of quails. Chantiratikul et al [15] reported the Se from selenomethionine was more effective in increasing Se concentrations in the tissues of quails than Se from Se-enriched kale sprout and sodium selenite.…”
Section: Meat Quality and Compositionmentioning
confidence: 99%
“…[16] In addition, Se is a component of the enzyme glutathione peroxidase, which is a selenoenzyme responsible for fighting free radicals in muscle tissue, preventing oxidative damage by acting as a modulator of the immune system and reproductive system. [17] There are many studies in the literature which have tested Se addition in quails' diets to improve the oxidative stability of the meat, however the antioxidant role of Se is still unclear [12,15] and the effects of organic or inorganic Se as dietary supplementation on its final concentration in quail meat and on the meat quality are not conclusive. [16,18] In fact, the role of SeY supplementation in quails' diets has not yet been elucidated in the literature, and more specifically there are no studies on the possible synergistic action between soybean oil (SO) and SeY on lipids, fatty acids, and the oxidative stability of meat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium levels increasing in poultry diet, its concentration in poultry products, in particular meat and eggs increases (Fisinin et. al., 2009;Bennett & Cheng, 2010;Chantiratikul et. al., 2020).…”
Section: Selenium In Poultry Breeding Productsmentioning
confidence: 99%